Islamic law from historical foundations to contemporary practice - Dien, M. Izzi (Edinburgh Univ. Press, 2004)
This survey of Islamic Law combines Western and Islamic views and describes the relationship between the original theories of Islamic law and the views of contemporary Islamic writers.